Paparan Kebisingan dan Perubahan Tekanan Darah Pekerja Di Bagian Kilang Area PT. Pertamina RU II Dumai - Nadia Arini; Bambang Wispriyono; Taufik Ashar (Jurnal Kesehatan Lingkungan, 2021)
Noise is one of the factors that can affect worker productivity. High noise intensity in the workplace can affect blood pressure. Every workplace always contains various hazard factors that can affect the health of workers. The purpose of this study was to determine the relationship between noise levels and blood pressure in workers at PT. Pertamina RU II. This research is an analytic study using a study design. The population sampled in this study is 130 people. The results showed that the noise intensity in the refinery area exceeded the NAB by 87 dbA, and in the office by 30-40 dbA. The workers' systolic blood pressure increased by 75%, diastolic blood pressure increased by 70%, and pulse rate increased by 89%. . The results of blood pressure in the study in two groups, namely exposed and unexposed, there was no significant difference between systolic and diastolic pressure in the exposed and unexposed groups of noise, but there was a significant difference between the difference in pulse rates in the exposed and unexposed groups. noise in the refinery area of ​​PT. Pertamina RU II Dumai